Comparing the clinical characteristics and risk factors of prognosis in pediatric ARDS with and without malignancies: a retrospective cohort study - Xi Xiong; Yun Cui; Chunxia Wang; Yiping Zhou; Xiaoxuan Ma; Pin Li; Yucai Zhang (BMC Pulmonary Medicine)
Abstract Background The number of malignancy patients with respiratory failure is rising in pediatric intensive care units (PICU). Our study aims to compare the clinical characteristics and prognostic risk factors of acute respiratory distress syndrome (ARDS) with or without malignancies. Methods This retrospective study reviewed medical records of 188 ARDS patients admitted to the PICU between January 2018 and December 2022, including 60 with malignancies and 128 without. Clinical data were collected within 48 h post-ARDS diagnosis. Multivariate logistic regression analysis and receiver operating characteristic curve (ROC) analysis were used to investigate the risk factors for PICU mortality in the malignancy and non-malignancy groups. Results Compared with pediatric patients without malignancy, the ARDS patients with malignancy presented higher mortality (55.0% vs. 31.3%, P = 0.002), a higher incidence of community-acquired fungal infection (36.1% vs. 6.3%, P < 0.001) and multidrug resistance (MDR) bacteria (65.4% vs. 30.5%, P = 0.003). There were substantial differences in levels of lactate [1.5 (0.8–3.7) vs. 1.0 (0.7-2.0) mmol/L, P = 0.008], C-reactive protein (CRP) [150.0 (83.0-168.0) vs. 31.0 (10.0-108.0) mg/L, P = 0.02], procalcitonin (PCT) [10.4 (2.0-27.5) vs. 1.2 (0.3–6.2) mg/L, P < 0.001], counts of platelet [17.0 (8.0–73.0) vs. 232.0 (152.0-330.0) × 109/µL, P < 0.001], the distribution of CD8 + T [36.9 (26.0-53.6) vs. 21.9 (17.3–29.1) %, P < 0.001], CD19 + T cells [9.9 (0.9–30.2) vs. 33.6 (22-46.6) %, P < 0.001], and higher peak vasoactive–inotropic score (VIS) in ARDS with malignancy [73.0 (20–208) vs. 15.0 (5.0–82.0), P < 0.01]. In multivariable analysis, only VIS independently predicted mortality in ARDS patients with malignancy (OR, 1.011; 95% confidence interval [CI]: 1.003–1.018; P = 0.005). Neither pSOFA scores (OR, 1.249, 95% CI: 0.958–1.628, P = 0.101) nor lactate levels (OR, 1.192, 95% CI: 0.928–1.531, P = 0.170) showed significant associations. Conclusion ARDS patients with malignancies exhibited poorer outcomes. VIS is only an independent predictor of mortality in pediatric ARDS patients with malignancies.